The mummy returns [videorecording (DVD)] - Sommers, Stephen; Fraser, Brendan, 1968-; Weisz, Rachel, 1970-; Hannah, John, 1962-; Vosloo, Arnold; Fehr, Oded, 1970-; Johnson, Dwayne, 1972- (Universal, 2017)
It's now 1933, 10 years after Rick and Evie met. They're married, settled in London and are raising their 8 year old son, Alex. Imhotep's corpse has been brought to the British Museum, and resurrected; the mummy walks the earth again, determined to become immortal. Another force born of the darkest rituals of ancient Egyptian mysticism, even more powerful than Imhotep, has also been set loose in the world. When these two forces clash, the world will hang in the balance, sending the O'Connells on a desperate race to save the world, and rescue their son.